2010
DOI: 10.1186/1475-2891-9-8
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in individuals with metabolic syndrome given DASH diet counseling when provided a low sodium vegetable juice: a randomized controlled trial

Abstract: BackgroundMetabolic syndrome, a constellation of metabolic risk factors for type 2 diabetes and cardiovascular disease, is one of the fastest growing disease entities in the world. Weight loss is thought to be a key to improving all aspects of metabolic syndrome. Research studies have suggested benefits from diets rich in vegetables and fruits in helping individuals reach and achieve healthy weights.ObjectiveTo evaluate the effects of a ready to serve vegetable juice as part of a calorie-appropriate Dietary Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 50 publications
(56 reference statements)
0
28
0
5
Order By: Relevance
“…This lack of change that occurred in our study could be attributed to the population cohort. It has been found that obese women have higher muscle strength measures when compared to lean women, which could have attributed to this lack of change (32).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This lack of change that occurred in our study could be attributed to the population cohort. It has been found that obese women have higher muscle strength measures when compared to lean women, which could have attributed to this lack of change (32).…”
Section: Discussionmentioning
confidence: 99%
“…The DASH diet has been shown to result in weight loss and reduce hypertension, however, these results have not been shown in individuals who have chronic conditions such as metabolic syndrome [32]. Metabolic syndrome is a collection of metabolic risk factors for cardiovascular disease and type 2 diabetes [32].…”
Section: Dash Diet and Older Adultsmentioning
confidence: 99%
See 3 more Smart Citations